Working Capital Management and Firm Performance: Evidence from Non-Financial Firms in Pakistan - Siraj, Mohsin; Mubeen, Muhammad; Sarwat, Salman (Asian Journal of Empirical Research, 2019)
This study analyzes the effects of Working Capital management i.e. inventory management, receivable management and payable management, on the performance of the non-financial firms in Pakistan. Panel data of 280 nonfinancial firms enlisted in Pakistan Stock Exchange have been analyzed from 2000 to 2016. Firms’ profitability were proximate with return on assets and return on equity; whereas for growth i.e. sales growth and asset growth were used. The impact of Working Capital management is captured through its constituent policies such as Inventory management, Receivable Management and Payable management. Firm size, liquidity and leverage are used as control variables. Results suggest that Working Capital management has a significant impact on firms’ financial performance in terms of profitability, as well as growth. As far as component wise results are concerned, inventory management does influence the firms’ growth and Payable management significantly, hence affecting the firms’ profitability. However, only receivable management influences both profitability and growth.